A novel evaluation of genetic polymorphism in BCG adenitis - Maryam Hassanzad; Poupak Farnia; Sepideh Darougar; Ali Akbar Velayati (The Turkish Journal of Pediatrics)
Bacillus Calmette-Guerin (BCG) is a live attenuated vaccine which has been used to prevent tuberculosis, according to the World Health Organization (WHO) recommendation in parts of the world with an incidence of tuberculosis infection more than 1%. The incidence of BCG adverse reactions differs between regions with regional lymphadenitis as the most common presentation. The aim of this study was to detect the impact of polymorphisms causing BCG lymphadenitis in children receiving BCG vaccination at birth. Eight healthy infants with BCG adenitis from 4 to 12 months old were enrolled. All these patients underwent a thorough physical examination, abdominopelvic ultrasound evaluation to detect distant lymphadenopathies and immunodeficiency screening tests for any possible underlying immunodeficiency disorders. Then genotyping for known mutations was performed using restriction fragments length polymorphism (PCR-RFLP) assays. Sequencing was performed for IL-12 Rβ1, IFN-ϒ receptor 1, IL-10, TNF-α and P2X7. The mean age of onset of the adenitis was 6.5 months. TNF-857, IL-12Rβ1 705, IL-10 1082, and IFN-ϒ- 56 single nucleotide polymorphisms (SNPs) were common in the children studied. The most frequent polymorphism found in the patients with BCG adenitis except one, was the P2X7 -762 polymorphism. To conclude, these polymorphisms are more common in some ethnic populations but not others and make the genetic basis of immunity to BCG strains and the occurrence of post-BCG lymphadenitis in otherwise healthy children.